Both Quadriceps and Bone-Patellar Tendon-Bone Autografts Improve Postoperative Stability and Functional Outcomes After Anterior Cruciate Ligament Reconstruction: A Systematic Review - Udit Dave, B.S; Sione A. Ofa, M.D; Victoria K. Ierulli, M.S; Andre Perez-Chaumont, M.D; Mary K. Mulcahey, M.D (Elsevier, 2024)
Purpose: To compare postoperative knee stability, functional outcomes, and complications after anterior cruciate ligament (ACL) reconstruction using bone-patellar tendon-bone (BPTB) versus quadriceps tendon autograft. Methods: In accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines, the PubMed, Embase, and Cochrane Library databases were searched for studies published in 2002 or later. Studies were included if they met the following criteria: randomized controlled trials that included patients who underwent ACL reconstruction with BPTB or quadriceps tendon autograft including all soft tissue and bone-quadriceps tendon and in which measures of postoperative stability and functional outcomes were reported. Studies that were not written in English and those that analyzed animals or cadavers, were not randomized controlled trials, or used other grafts (e.g., hamstring) were excluded. Results: The initial search identified 348 studies, 6 of which were included in this systematic review. Two of the six studies found no significant difference in performance outcomes or complications between quadriceps and BPTB autografts. One study found that patients receiving quadriceps autograft self-reported improved knee functional status compared with those receiving BPTB autograft. Another study found that quadriceps autograft resulted in a significantly reduced Quadriceps Index postoperatively compared with BPTB autograft (69.5 vs 82.8, P = .01) but found no difference in postoperative quadriceps strength. An additional study found that the outcomes of quadriceps tendon and BPTB autografts were equivalent per the International Knee Documentation Committee scale, but anterior knee pain was less severe in patients with quadriceps tendon autograft. Furthermore, one study revealed the overall International Knee Documentation Committee score was reported as normal significantly more often in patients who underwent ACL reconstruction with BPTB autograft (85% vs 50%, P < .001) and that donor-site morbidity was greater in patients with quadriceps autograft. No significant difference was found in complications requiring reoperation across studies. Conclusions: Patients undergoing ACL reconstruction with either BPTB or quadriceps tendon autograft reported improved postoperative knee stability and functional outcomes. There is no significant difference in complications between quadriceps autograft use and BPTB autograft use. Level of Evidence: Level III, systematic review of Level III retrospective studies.